IMPROVING LOCAL PROCESSING TRAFFIC VOLUMES IN RAILWAY JUNCTIONS - Levytskyi, I. Ye.; Korobova, R. H. (Science and Transport Progress, 2008)
The analysis of tendencies of development of railway junctions is performed. The method of optimization of distributing the sorting work between sorting and freight stations with the domestic cars in the railway junctions is presented.